Effect of post heat treatment on the microstructure and microhardness of diffusion coupled gray cast iron and low carbon steel - Ayob, F. (Institute of Physics Publishing, 2018)
Experimental studies carried out on the joining of grey lamellar graphite cast iron to low carbon steel by diffusion welding techniques had successfully produced a few diffusion couples, despite facing some earlier failures. Although faced with some success, analysis on the diffusion couples showed voids and incomplete bond/joint at the interface of the joints while the tensile strength value was found to be low. In furtherance, the diffusion couples were then subjected to a post-weld heat treatment (PWHT) that allowed for further diffusion process to take place to remove the voids and complete the bond/weld. The results revealed microvoids and interface lines at the interfaces of the specimens treated at temperatures of 800°C, and becoming less visible at 900°C. At an elevated temperature of 1000°C, on longer treatment times, apparently these microvoids and interface lines had disappeared, and the bond/weld at the interfaces of the diffusional welded couples seemed to be more complete. Thus, heat treatment time and temperature were found to have a strong influence on the structure, thickness and hardness of the diffusion layer produced. © Published under licence by IOP Publishing Ltd.